Credit Composition and Subnational Economic Growth: Long-Run and Short-Run Evidence from East Nusa Tenggara - Ketmoen, Adrianus; Pongge, Maria Imakulata; Leki, Salomon; Lodo, Angela Jeni (Signifikan: Jurnal Ilmu Ekonomi, 2026)
Research Originality. This study advances the finance–growth nexus literature by providing subnational time-series evidence on credit composition rather than aggregate credit, focusing on a structurally developing province in Eastern Indonesia. Research Objectives. This study examines whether different types of bank credit contribute differently to regional economic growth in East Nusa Tenggara. Research Methods. This study applies the Autoregressive Distributed Lag (ARDL) approach. The ARDL Bounds Test is employed to verify cointegration, followed by Error Correction Model (ECM) estimation and diagnostic stability tests. Empirical Results. The findings confirm a significant long-run relationship between credit composition and regional economic growth. Consumer credit exhibits a positive long-run effect on real GRDP, while investment credit shows a moderate impact. Working capital credit does not demonstrate a significant long-run contribution. Implications. The results suggest that not only the volume but also the credit allocation structure plays a crucial role in shaping regional economic performance. Policy strategies in developing regions should therefore emphasize productive and demand-supporting credit allocation to promote sustainable growth. JEL Classification: E44, O16, O47, R11